Historical prevalence of infectious diseases and entrepreneurship: Evidence from 125 countries - Messono O. Omang; Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
Purpose -This investigates the effects of the historical prevalence of infectious diseases on contemporary entrepreneurship. Previous studies reveal numerous proximate causes of entrepreneurship, but little is known about the fundamental determinants of this widespread economic concern. Design/methodology/approach -The central hypothesis is that historical pathogens exert persistent impacts on present-day entrepreneurship. We provide support for the underlying hypothesis using Ordinary Least Squares (OLS) and Two Stage Least Squares (2SLS) with cross-sectional data from 125 countries consisting of the averages between 2006 and 2018. Findings -Past diseases reduce entrepreneurship both directly and indirectly. The strongest indirect effects occur through GDP per capita, property rights, innovation, entrepreneurial attitudes, entrepreneurial abilities, entrepreneurial aspirations, and skills. This result is robust to many sensitivity tests. Policy makers may take these findings into account and incorporate disease pathogens into the design of entrepreneurship. Originality/value -The novelty of this paper lies in the adoption of a historical approach that sheds light on the deep historical roots of cross-country differences in entrepreneurship.
Keywords: I0; J24; I21; I31; 330; entrepreneurship; diseases; property rights; innovation